To Die on Ambae: On the Possibility of doing Fieldwork Forever - Rodman, William L. (Anthropologica, 2022)
"To Die on Ambae ..." is ethnography cast in the form of a narrative, a "true fiction" about illness in the context of fieldwork on a remote Pacific Island. We reflect on the way in which our direct involvement in the politics of curing shed new light on our relationships with people in our host community. We also deal with some of the hidden costs of fieldwork, both for anthropologists and for the people they study. Implicitly, we seek to contribute to discussion of three current issues in interpretive anthropology: the points of interface between fiction and ethnography, the representation of reflexivity in ethnographic writing, and the uses of dialogue and multiple voices in ethnographic narrative.